Sensitivity analysis in interval-valued trapezoidal fuzzy number linear programming problems - Farhadinia, B. (Applied mathematical modelling, 2014)
The aim of this article is to introduce a formulation of fuzzy linear programming problems involving the level (hL,hU)-interval-valued trapezoidal fuzzy numbers as parameters. Indeed, such a formulation is the general form of trapezoidal fuzzy number linear programming problems. Then, it is demonstrated that study of the sensitivity analysis for the level (hL,hU)-interval-valued trapezoidal fuzzy number linear programming problems gives rise to the same expected results as those obtained for trapezoidal fuzzy number linear programming problems.